2002
DOI: 10.1029/2001jd002013
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving aerosol optical depth and type in the boundary layer over land and ocean from simultaneous GOME spectrometer and ATSR‐2 radiometer measurements, 1, Method description

Abstract: A new aerosol retrieval method called Synergetic Aerosol Retrieval (SYNAER), using simultaneous measurements of the radiometer Along Track Scanning Radiometer (ATSR‐2) and the spectrometer Global Ozone Monitoring Experiment (GOME) in the visible and near‐infrared spectra, was developed. Both instruments are flown onboard the European Remote Sensing (ERS‐2) satellite. SYNAER delivers boundary layer aerosol optical thickness (BLAOT) and aerosol type both over land and over ocean, the latter as BLAOT percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…Table 1 in Holzer-Popp et al (2002) gives percentage contributions to the total optical depth of the respective mixtures by the basic components: water soluble, water insoluble, sea salt accumulation mode, coarse mode, soot, and mineral transported. It is used as a guide for converting MACC species into types.…”
Section: Aerosols Propertiesmentioning
confidence: 99%
“…Table 1 in Holzer-Popp et al (2002) gives percentage contributions to the total optical depth of the respective mixtures by the basic components: water soluble, water insoluble, sea salt accumulation mode, coarse mode, soot, and mineral transported. It is used as a guide for converting MACC species into types.…”
Section: Aerosols Propertiesmentioning
confidence: 99%
“…Previous studies show that certain relationships between the surface reflectance at visible channels (0.67 Remote Sens. 2017, 9, 253 5 of 21 and 0.47 µm) and reflectance at near-infrared/ infrared channels (e.g., 0.86, 1.6, 2.1 and 3.75 µm) can be found for certain surface types depending on instruments [5,6,[38][39][40]. Figure 2 shows an example of the relationships between the spectral surface reflectance at visible and near-infrared channels for different surface types over China.…”
Section: Surface Parameterizationmentioning
confidence: 99%
“…One year (2008) cloud-free MODIS C6 TOA reflectance and corresponding MODIS surface reflectance product (MOD09A1) were collected over the study region as shown in Figure 1. Previous studies show that certain relationships between the surface reflectance at visible channels (0.67 and 0.47 µm) and reflectance at near-infrared/ infrared channels (e.g., 0.86, 1.6, 2.1 and 3.75 µm) can be found for certain surface types depending on instruments [5,6,[38][39][40]. Figure 2 shows an Previous attempts show the possibilities of using MODIS data product for surface parameterization and atmospheric parameters retrieval for instruments like Landsat (similar to GF4) [26,37].…”
Section: Surface Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile the Synergetic Aerosol Retrieval (SYNAER, Holzer-Popp et al, 2002a, b, 2008 provides aerosol optical depth observations from ENVISAT (Environmental Satellite) Advanced Along Track Scanning Radiometer (AATSR) and Scanning Imaging Absorption Spectrometer for Atmospheric CHartographY (SCIAMACHY) separately for the soot, mineral, water soluble, water insoluble and sea salt components. This opens the possibility to assimilate aerosols in a component-wise approach over both land and ocean.…”
Section: Introductionmentioning
confidence: 99%